Effectiveness of sweep net, yellow pan trap and malaise trap for sampling parasitic hymenoptera on tidal swamp rice - Zahlul Ikhsan; Hidrayani Hidrayani; Yaherwandi Yaherwandi; Hasmiandy Hamid (Aceh Journal of Animal Science, 2021)
The presence of the parasitic Hymenoptera plays a vital role in pest management for sustainable agriculture. So, it is crucial to know the parasitoid species that exist in an agroecosystem. Sweep Net, Yellow Pan Trap, and Malaise Trap are often used to study the diversity of Hymenoptera parasitic in agroecosystems. This study aims to see the effectiveness of Sweep Net, Yellow Pan Trap, and Malaise Trap in trapping Parasitic Hymenoptera. The study was carried out at four sub-districts, namely are Batang Tuaka, Keritang, Reteh, and Tembilahan Hulu sub-district. The research was carried out by sampling with the transect line method. Sweep net, Yellow pan trap, and Malaise trap have trapped 5,732 individuals of Parasitic Hymenoptera on tidal swamp rice in Indragiri Hilir Regency. The Parasitic Hymenoptera consists of 10 superfamilies, 30 families, and 320 morphospecies. Malaise traps are the best for trapping parasitic Hymenoptera on tidal swamp rice. Malaise traps have been able to trap up to 62% of morphospecies and 81% of the abundance of individual Parasitic Hymenoptera on tidal swamp rice. Yellow pan traps trap 28% of morphospecies and 15% of the abundance of individual Parasitic Hymenoptera. The sweep net can trap 10% of morphospecies and 4% of the abundance of individual Parasitic Hymenoptera.Keywords: Parasitic Hymenoptera; trap; tidal swamp rice.